2022
DOI: 10.1017/dsj.2022.24
|View full text |Cite
|
Sign up to set email alerts
|

An introduction to radical participatory design: decolonising participatory design processes

Abstract: Outside of community-led design projects, most participatory design processes initiated by a company or organisation maintain or even strengthen power imbalances between the design organisation and the community on whose purported behalf they are designing, further increasing the absencing experience. Radical participatory design (RPD) is a radically relational answer to the coloniality inherent in participatory design where the community members’ disappointment is greater due to the greater expectations and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…When limitations are not explained ‘harm… occurs when agencies engage with women and girls but do not meet their concerns, particularly if agencies do not set clear expectations when they convene consultations’ (Anderson, p.33, 2020). Udoewa [ 27 ] writes that Coloniality is inherent in participatory design, wherein the community members’ ‘disappointment is greater due to the greater expectations and presencing [a field of co-creation and social warmth] potential of a ‘participatory design’ process’ (p.1). An example here was that although participants attested that field staff explained the project to them well, one shortcoming was its failure to explain its limitations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When limitations are not explained ‘harm… occurs when agencies engage with women and girls but do not meet their concerns, particularly if agencies do not set clear expectations when they convene consultations’ (Anderson, p.33, 2020). Udoewa [ 27 ] writes that Coloniality is inherent in participatory design, wherein the community members’ ‘disappointment is greater due to the greater expectations and presencing [a field of co-creation and social warmth] potential of a ‘participatory design’ process’ (p.1). An example here was that although participants attested that field staff explained the project to them well, one shortcoming was its failure to explain its limitations.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the challenge of informing participants ‘especially in postcolonial and other settings with power inequalities, because of cultural differences and social injustices, including the systematic denial of information, autonomy and rights for people with limited power’ [ 3 ], p.814). An alternative is ‘radical participatory design’ – that which ‘fully includes the community members in all activities of all phases of the design process and in all interpretation, decision-making, and planning between design activities’ [ 27 ]. This approach could work in this protracted setting as the need for humanitarianism transforms into the need for development and sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…According to Noel (2022), liberatory design pedagogies: 1) cultivate critical questioning of the self and the systems within which students are embedded and 2) prompt collective, iterative actions intended to transform (3). On the other hand, courses integrating DT practices to cultivate students-as-designers can perpetuate colonial practices and reinforce inequitable power dynamics between students and those they design with and for (Udoewa 2022). Interviewing and observation practices within researchbased DT course projects can be used to extract knowledge from communities in order to advance problematic institutional priorities, research interests, course learning goals, or profit margins (Akama, Hagen, and Whaanga-Schollum 2019;Escobar 2018;Grimes et al 2021;Irani 2018;Jamal, Kircher, and Donaldson 2021;Rittner 2020;Shahjahan et al 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although prior studies have shown DT can positively impact teaching and learning within higher education (Haigh and Withell 2020;Lake, Flannery, and Kearns 2021;Lake, Lehman, and Chamberlain 2019;Lake, Motley, and Moner 2019;McLaughlin et al 2022;Pope-Ruark, Motley, and Moner 2019), little research has explored the potential role of DT when it comes to liberatory teaching and learning praxis and philosophies (Noel 2022;Udoewa 2022). In addition, few studies analyze data from the perspectives of faculty and student within multiple disciplines and institutions of higher education.…”
Section: Introductionmentioning
confidence: 99%
“…Working with true and deep participatory approaches (e.g. Godrie et al, 2022;Udoewa, 2022) represents a starting point to operationalise the approach in concrete praxis.…”
Section: Open Cooperation Through Open Educationmentioning
confidence: 99%